Citizen-engaged screening of 230 pesticides in the Lake Naivasha catchment, Kenya, using stir bar sorptive extraction and GC-QToF-HRMS - Cacciatori, Caterina; Mariani, Giulio; Comero, Sara; Kiminta, Enock; Salyani, Anham; Myers, Jackie; Pettigrove, Vincent; Gawlik, Bernd Manfred (Frontiers in Environmental Science, 2025)
The presence of pesticides in surface water samples from the Lake Naivasha catchment area in Kenya was investigated using Stir Bar Sorptive Extraction (SBSE) and Gas Chromatograph with Quadruple Time-Of-Flight High Resolution Mass Spectrometry (GC-QToF-HRMS). A total of 56 pesticides were detected, belonging to different classes including fungicides (48.2%), insecticides (17.9%), herbicides (12.5%), and other categories. The most frequently detected pesticides were the fungicides boscalid, fluopyram, hexachlorobenzene, tebuconazole, herbicide metolachlor, and insecticides bromopropylate, chlorpyrifos, diazinon, and the synergist piperonyl butoxide. The site with the highest pesticides detections was adjacent to Lake Naivasha, near a wastewater treatment plant discharge. Toxicological risk assessments revealed that the acute toxic unit threshold for crustaceans (TU = 0.01) was exceeded in several samples, primarily due to the presence of chlorpyrifos and diazinon. Notably, chlorpyrifos, banned for all agricultural purposes in Kenya in 2024, was detected in several samples. These findings highlight the presence of pesticides in Kenyan water bodies, posing potential risks to aquatic ecosystems and underscore a need for stricter regulation, ongoing monitoring, and the adoption of sustainable agricultural practices to minimise the impact of pesticides on the environment.